A convenient and practical heterogeneous palladium‐catalyzed carbonylative Suzuki coupling of aryl iodides with formic acid as carbon monoxide source. (11th December 2018) - You, Shengyong; Yan, Chenyu; Zhang, Rongli; Cai, Mingzhong
Abstract : A practical heterogeneous palladium‐catalyzed carbonylative Suzuki coupling of aryl iodides with arylboronic acids under carbon monoxide gas‐free conditions has been developed using a bidentate phosphino‐functionalized magnetic nanoparticle‐immobilized palladium(II) complex as catalyst. Formic acid was utilized as the carbon monoxide source with dicyclohexylcarbodiimide as the activator, and a wide variety of biaryl ketones were generated in moderate to high yields. The new heterogeneous palladium catalyst can be prepared via a simple procedure and can easily be separated from a reaction mixture by simply applying an external magnet and recycled up to 10 times without any loss of activity. Abstract : A general and practical heterogeneous palladium‐catalyzed carbonylative Suzuki coupling of aryl iodides with arylboronic acids under carbon monoxide gas‐free conditions has been developed using a recyclable magnetic nanoparticle‐immobilized bidentate phosphine palladium(II) complex as catalyst and formic acid as the carbon monoxide source, yielding a wide variety of biaryl ketones in moderate to high yields.